The Effect of Conditional Conservatism and Agency Cost on Investment-Cashflow Sensitivity - Wibawa, Bima Abdi; Wardhani, Ratna (Universitas Prasetiya Mulya, 2017)
This research aims to give empirical evidence of the effect of conditional conservatism on company’s investment-cashflow sensitivity, and whether the impact is stronger in high agency cost firms compare to in low agency cost firms. This research uses dividend payout ratio to measure the agency cost, because this study uses Indonesia as a research context where companies in Indonesia majority have concentrated ownership and funding through debt so that agency conflict that appears more dominant is the conflict of agency type two and three. This study uses sample from manufacturing companies listed in Indonesia Stock Exchange during the period 2008-2012. The total observation in this research is 474 firm years, which 152 of the samples is classified as high agency cost firms and 322 sample as low agency cost firms. The result shows that as the recognition of economic losses becomes more timely, the sensitivity of firm investment to cashflow decreases. Conditional conservatism decreases investment-cashflow sensitivity in low agency cost firms but increases the sensitivity in high agency cost firms. In fact, before implementation of conditional conservatism, high agency cost firms have smaller investment-cashflow sensitivity compared to the low agency cost one.